Pengaruh Environmental Performance terhadap Economic Performance (Studi Empiris pada Perusahaan Manufaktur Tahun 2016-2017) - Riska Nur Aisiyah (Academica: Journal of Multidisciplinary Studies, 2018)
This research aims to determine the impact of the company’s environmental performance on the company’s economic performance. Independent variables in this study are environmental performance measured by PROPER scores, while the dependencies of the variables are economic performance measured using ROA. With a quantitative approach, hypotheses in the study were tested using regression analysis. The samples in this study were 41 manufacturing companies selected using purposive-sampling techniques. The results of this study show that environmental performance has no effect on the company’s economic performance.Keywords: environmental, economic, performance